The Impact of the Epithelial–Mesenchymal Transition Regulator Hepatocyte Growth Factor Receptor/Met on Skin Immunity by Modulating Langerhans Cell Migration - Sagi, Zsofia; Hieronymus, Thomas (Frontiers in Immunology, 2018)
Langerhans cells (LCs), the epidermal dendritic cell (DC) subset, express the transmembrane tyrosine kinase receptor Met also known as hepatocyte growth factor (HGF) receptor. HGF is the exclusive ligand of Met and upon binding executes mitogenic, morphogenic, and motogenic activities to various cells. HGF exerts anti-inflammatory activities via Met-signaling and was found to regulate various functions of immune cells, including differentiation and maturation, cytokine production, cellular migration and adhesion, and T cell effector function. It has only recently become evident that a number of HGF-regulated functions in inflammatory processes and immune responses are imparted via DCs. However, the mechanisms by which Met-signaling in DCs conveys its immunoregulatory effects have not yet been fully understood. In this review, we focus on the current knowledge of Met-signaling in DCs with particular attention on the morphogenic and motogenic activities. Met-signaling was shown to promote DC mobility by regulating matrix metalloproteinase (MMP) activities and adhesion. This is a striking resemblance to the role of Met in regulating a cell fate program during embryonic development, wound healing, and in tumor invasion known as epithelial-mesenchymal transition (EMT). Hence, we propose the concept that an EMT program is executed by Met-signaling in LCs.